Breaking down gender subtype perception - Kristina Dziallas; Martin Borkovec (Technium Social Sciences Journal, 2020)
Gender stereotype research has identified many female and male subtypes, e.g. housewife, career woman, macho man, and wimp. Regarding their perception, several dimensions, such as Warmth, Competence, Traditionality, and Age, have been found to be meaningful in people’s cognitive organization of them. The present paper analyses gender subtype perception results obtained in an online questionnaire among English and Spanish participants who rated ten female and ten male subtypes on 15 scales. The subtypes were produced by the participants themselves in a prior study. The results are backed up by interview quotes of the same participants. Many of the findings conform to those of prior studies, e.g. the clear separation of female and male subtype clusters, while others are novel or contrary to previous research. Thus, the English male subtype mate is perceived both very masculine and feminine and the Spanish promiscuous female subtype guarra is seen as inherently different from the English equivalents.